KAJIAN KEHILANGAN HASIL PADA PEMANENAN PADI SAWAH MENGGUNAKAN MESIN MINI COMBINE HARVESTER MAXXI-M (Studi Kasus di DesaTorout Kecamatan Tompaso Baru Kabupaten Minahasa Selatan) - Valentinus T. Pondan; L.C.Ch.E. Lengkey; D. Ludong (Universitas Sam Ratulangi, 2016)
ABSTRACTThe purpose of this study was to determine the amount of loss of rice at harvest time, lostbecause it is not harvested, lost because of lagging on the machine, lost in the threshing. andthe capacity and efficiency in the field using the Mini Combine Harvester. Research wasconducted during April-May 2016, in the of Torout village, South Minahasa district. UsedSako rice which is the local varieties. Mini Combine Harvester Maxxi Type-M is used as aharvesting machine. Results showed that losses at the stage of harvesting or cutting, (2.09 ±0.81)%, standing crop loss (1.08 ± 0.17)%, un-thressed loss (1.44 ± 0.40)% and the threshingloss (0.003 ± 0.002)%.